Rare Gas Fission Yields of Am241 and Am242 - Pleva, James Francis (My University, 1967)
The yields of xenon and krypton from the neutron- induced fission of Am241 and Am242 have been measured with a mass spectrometer. This was accomplished by irradiating samples of Am241 for different lengths of time so that the effect of the growth of highly fissionable Am242 could be determined. These studies reveal that both the degree of fine structure in the mass yield curve and the fission-product charge distribution are dependent on the energy of the incident neutrons. This has not been previously observed for any fissioning nuclide. These studies also reveal effects of the 50-neutron shell and of the neutron-proton ratio of the fissioning nuclide on the mass yield curve.
Keywords: rare gas, fission, xenon, krypton, yield curve, neutron, shell